CONSULTING AS A STRATEGY TO HELP FUTURE YOUNG ENTREPRENEURS (Innovative professional education, 2023)
The publication highlights the problems of youth entrepreneurship development. One of the forms of support for future young entrepreneurs is counseling, which should promote the acquisition of knowledge about creating employment opportunities for young people, provided they actively participate in youth entrepreneurship. Promoting youth entrepreneurship has potential for social development as it gives young people the opportunity to increase their level of protection against unemployment and self-employment, creating jobs for others, thereby raising their living standards and those around them, while reducing poverty and creating sustainable livelihoods to existence Based on the results of the study, it is concluded that the too small role of young people in entrepreneurship is likely to continue to cause concern among stakeholders, if in the process of mastering the basics of entrepreneurship and financial literacy, effective counseling is not introduced to solve these problems.
Keywords: young entrepreneur, unemployment, self-employment, educational policy, teaching staff, employers